Effects of contracting out employment services: Evidence from a randomized experiment - Helge Bennmarker; Erik Grönqvist; Björn Öckert (Uppsala University, Department of Economics, 2012)
In many countries welfare services that traditionally have been provided by the public sector are being contracted out to private providers. But are private contractors better at providing these services? We use a randomized experiment to empirically assess the effectiveness of contracting out employment services to private placement agencies. Our results show that unemployed at private placement agencies have a closer interaction with their case worker than unemployed at the Public Employment Service (PES); e.g., they receive more assistance in improving their job search technology. We do not find any overall difference in the chances of finding employment between private placement agencies and the PES, but this hides important heterogeneities across different types of unemployed. In particular, private providers are better at providing employment services to immigrants, whereas they may be worse for adolescents. Any effects tend to fade away over time.
Keywords: H44; J68; L33; 330; Job placement; Contracting out; Randomized experiment; Arbeitsvermittlung; Privatwirtschaft; Öffentlicher Sektor; Dienstleistungsqualität; Schweden